2002
DOI: 10.1103/physrevb.65.205315
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of a two-dimensional electron gas in semiconductor thin films at low temperatures: Role of acoustic phonon confinement

Abstract: We study the effect of acoustic-phonon confinement on the energy and momentum relaxation of a twodimensional electron gas in thin films. The interaction via the deformation and piezoelectric potentials with a complete set of phonon modes in films with stress-free and rigid surfaces is taken into account. We demonstrate that in thin films the modification of the phonon properties and screening brings about substantial changes of the electron relaxation rates in comparison to the case of interaction with bulk ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…The principal characteristic of the electron gas is that due to the quantization of the wavevector component perpendicular to the film surfaces the electron gas forms quasi 2D sub-bands, which are specific to a quantum well (QW) formalism. 16,21,22,26 In an accompanying paper we describe the electrons as a 3D Fermi gas. We choose a range of parameters L, T e (electrons temperature), and T ph (lattice temperature) such that the phonon gas has a quasi two-dimensional distribution (for L = 100 nm we took T e, T ph ≤ 0.2 K).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The principal characteristic of the electron gas is that due to the quantization of the wavevector component perpendicular to the film surfaces the electron gas forms quasi 2D sub-bands, which are specific to a quantum well (QW) formalism. 16,21,22,26 In an accompanying paper we describe the electrons as a 3D Fermi gas. We choose a range of parameters L, T e (electrons temperature), and T ph (lattice temperature) such that the phonon gas has a quasi two-dimensional distribution (for L = 100 nm we took T e, T ph ≤ 0.2 K).…”
Section: Discussionmentioning
confidence: 99%
“…Such a sharp oscillatory behavior is a characteristic of the QW description of the electronic states in the metallic films 16,21,22,26 and could be useful for applications, like thickness variation detection or surface contamination. Moreover, by varying the thickness of the membrane one might vary dramatically the electronphonon coupling and, through this, the thermalisation or the noise level in the system.…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…4 It has also been previously used, in form of a shifted Fermi-Dirac ͑FD͒ distribution, in single-subband electron-transport calculations in quantum wells. 5 In this work we apply such a model to systems with a number of size-quantized subbands and assume that each of them will have the same form of shifted-MB distribution over the inplane wave vectors, which is then used to evaluate the distribution-averaged intersubband scattering rates, Eq. ͑9.153͒ from Ref.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…31,32 Hu et al 33 reported the enhancement of electron coherence transport when Nb 3 SiTe 6 crystals were reduced to below a few unit cells in thickness. This is because of a phonon dimension crossover from 3D to 2D in ultra-thin films, which leads to a weakening of the e-ph interactions.…”
mentioning
confidence: 99%